The effectiveness of Pencak Silat to change teenage personalities - Tjung Hauw Sin; Nurul Ihsan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
This study aims to look at the effect of martial arts exercises on changes in adolescent personality. The sample of this study was Yadika Lubuklinggau High School students who participated in pencak silat extracurricular activities, totaling 22 people. The sampling technique is a total sampling technique. The hypothesis proposed in this study is that martial arts exercises provide a significant influence on changes in adolescent personality. The design of this study is one group pretest-posttest. Data collection techniques using a questionnaire with Likert Scale. The data in this study are the answers of the sample parents regarding their daily personalities both before and after pencak silat training. Hypothesis testing with a t-test at a significant level of 0.05%. Based on testing the research hypothesis using the t-test statistical analysis it is known that the t-value is 3,227, while the t-table value is 1,720. Thus, it can be concluded that the hypothesis proposed in this study was accepted. The conclusion that can be drawn in this study is that martial arts exercises provide effects on changes in adolescent personality.